Seven new species of Phyllocoptini from Tibet Autonomous Region, China (Acari: Eriophyidae: Phyllocoptinae) - Song, Zi-Wei; Xue, Xiao-Feng; Hong, Xiao-Yue (Zootaxa, 2009)
In this paper, seven new species of the Phyllocoptini (Acari: Eriophyidae: Phyllocoptinae) from China are described and illustrated. They are Calvittacus swidanus sp. nov. on Swida macrophylla (Cornaceae); Vasates desmodius sp. nov. on Desmodium sp. (Fabaceae); Epitrimerus nyingchicus sp. nov. on Cotoneaster ambiguus (Rosaceae); Calepitrimerus painus sp. nov. on Rhododendron sp. (Ericaceae); Calepitrimerus cotoneaster sp. nov. on Cotoneaster buxifolius (Rosaceae); Phyllocoptruta deutzianus sp. nov. on Deutzia sp. (Saxifragaceae) and Phyllocoptruta smilanus sp. nov. on Smilax sp. (Liliaceae). All the eriophyoid mite species described here are vagrants on the undersurface of host leaves.